Juridical Analysis of Child Marriage Tolerance on Living Habits in Society Against Marriage Law - Mahaputri, Puang; Akib, Ma’ruf; Lanontji, Muryanto (JURNAL AKTA, 2025)
The diversity of the legal system in Indonesia triggers differences of views on the age limit of marriage between customary provisions and regulations in the law. The practice of people who still tolerate underage marriage is contrary to Law No. 16 of 2019, which expressly sets the age limit for marriage. This study aims to examine the position of customary law that still tolerates early marriage in the perspective of marriage law, and explore the possible limitations that can be applied by positive law to bridge the gap. This study uses normative legal research methods by examining various laws and regulations and related legal concepts. Data was obtained through literature studies sourced from laws and various articles relevant to the research topic. The results of the study show that customary law recognizes and provides space for the practice of child marriage, while the law provides that such tolerance can only be granted through the mechanism of marriage dispensation based on strong grounds. This difference of views requires dialogue and deliberation between traditional leaders and the government in order to achieve the harmonization of marriage law in Indonesia.